AUDIT SISTEM INFORMASI OPERASIONAL MENGGUNAKAN FRAMEWORK COBIT 5 (STUDI KASUS : BANK XYZ) - Supriady; Ginasta, Nava Gia; Hanum, Rahma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Bank XYZ is one of the BPD Banks. One of the strategies is to reduce the amount of investment and improve the quality of services in terms of information technology. The performance of the Operational Information System at Bank XYZ in serving customers will determine the quality of the services it provides. In conducting this research, the author uses the COBIT 5 framework with a DSS domain that combines control standards from many different sources in a single framework that can enable management to make control and control of the Information System environment. Gap analysis is the current capability level with the expected level of capability. Thus it can be seen how far the reach that must be achieved until the organization's goals are achieved. The results of the assessment and evaluation of the conformity of standards and operational management in the information technology system at Bank XYZ with the COBIT 5 framework with the results of the assessment of Bank XYZ current capabilities are at level 4 a predictable process. The result of level 4 is to ensure that the implementation of the process can support organizational goals.